Using Mobile Devices to Improve Speaking Fluency - Güçlü, Ramazan (Pegem Journal of Education and Instruction, 2025)
Abstract With recent advances in digital technologies and the ubiquitous use of mobile devices in daily life, effective oral practice outside the classroom is now a viable option for EFL learners. In line with Pegrum’s (2019) three mobilities framework, the present study reports on a group of EFL students who used their mobile devices (i.e., smartphones and tablets) to improve their speaking fluency beyond the classroom settings. More specifically, forty-four EFL students were asked to record a minimum of a two-minute speech each week outside the classroom over the course of 28 weeks. The analysis of the speech data and students’ perceptions of and experiences with the weekly speaking journal assignment carried out using mobile devices indicated that the EFL students achieved significant gains in fluency, which was measured by counting the number of words uttered per minute. Furthermore, students also acknowledged other advantages of this mobile oral practice in enhancing their self-confidence and decreasing speaking anxiety. The findings offer valuable implications for language learners and teachers, highlighting the fruitful effects of weekly mobile oral practice on the development of speaking fluency